On measures to protect domestic market and export support in conditions of preferential trade of the EAEU and Vietnam - Yu. G. Kirillov; E. K. Enza (Омский научный вестник: Серия "Общество. История. Современность")
The development of free trade of the Eurasian Economic Union with third countries does not exclude the creation of a mechanism to protect the domestic market for sensitive goods and maintaining the necessary balance of trade balances of the parties involved. The article analyzes the foreign trade cooperation between Russia and Vietnam in the development of the concluded Free Trade Agreement between the Eurasian Economic Union and its member states, on the one hand, and the Socialist Republic of Vietnam, on the other hand. The data presented indicate the need for regulatory influence aimed at protecting the domestic market of Russia maintaining appropriate proportions between domestic and imported goods. Certain measures for protecting the domestic market by the Eurasian Economic Commission in the context of preferential trade and national export stimulation measures are considered. The results can be used in the Eurasian Economic Union when building preferential relations with a number of states that have concluded or are ready in the near future to conclude such free trade agreements